2022
DOI: 10.2147/ijn.s354314
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal lncRNA HOTAIR Promotes the Progression and Angiogenesis of Endometriosis via the miR-761/HDAC1 Axis and Activation of STAT3-Mediated Inflammation

Abstract: Background Long non-coding RNA (lncRNA) and exosomes are implicated in endometriosis development. We measured the expression of an exosomal lncRNA, homeobox transcript antisense RNA (HOTAIR), and explored its molecular mechanism in endometriosis progression. Methods Expression of HOTAIR and microRNA (miR)-761 in different endometrial tissues was measured. Exosomes were isolated from a culture medium of endometrial stromal cells (ESCs). RT-qPCR was used to measure HOTAIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 43 publications
3
39
0
Order By: Relevance
“…In exosomes, it promotes proliferation, invasion, migration and inhibits the apoptosis of endometrial stromal cells. Acting as a competing endogenous RNA, it downregulates miR-761 and increase expression of its target gene HDAC1 [ 126 ]. It also plays an important role in EMT regulation in gastric cancer, switching the acetylation of H3K27 to methylation by the E cadherin promoter, which induces inhibition of E-cadherin transcription [ 61 ].…”
Section: Histone Modifications and Ncrnas: The Theorymentioning
confidence: 99%
“…In exosomes, it promotes proliferation, invasion, migration and inhibits the apoptosis of endometrial stromal cells. Acting as a competing endogenous RNA, it downregulates miR-761 and increase expression of its target gene HDAC1 [ 126 ]. It also plays an important role in EMT regulation in gastric cancer, switching the acetylation of H3K27 to methylation by the E cadherin promoter, which induces inhibition of E-cadherin transcription [ 61 ].…”
Section: Histone Modifications and Ncrnas: The Theorymentioning
confidence: 99%
“…Frontiers in Bioengineering and Biotechnology frontiersin.org characteristic of hydrogel and the ability to controlled-release its embedded molecule, encapsulation of exosomes with hydrogel provide an outstanding candidate in plenty of treatments including bone and cartilage regeneration, cardiovascular diseases, spinal cord injury, periodontal and corneal repairs (Xie et al, 2022). Exosome has immense potential of treating injured endometrium by regulating EMT (Yao et al, 2019;Feng et al, 2020), miRNA (Tan et al, 2020;Shi et al, 2021), proliferation (Lv et al, 2020) and endometrium angiogenesis (Zhang et al, 2022). However, all these effects are achieved via the suboptimal approach of direct injection which restricts the activity of exosomes by local tissue irritation or reduced self-life.…”
Section: Application Of Bioinspired Hydrogel As Exosome Delivery Systemmentioning
confidence: 99%
“…Compared with natural MSC-EVs, these engineered EVs show elevated abilities to promote blood vessel formation and reduce inflammation by weakening miR-383-induced VEGF downregulation [ 128 ]. HOX transcript antisense RNA (HOTAIR) has been reported to play critical roles in mediating the angiogenic effects of endothelial cells by enhancing VEGF expression and reversing miR-761-induced histone deacetylase 1 inhibition [ 129 , 130 ]. Born et al demonstrated that MSC treated with HOTAIR overexpression plasmids can produce EVs with increased HOTAIR content, which further accelerates angiogenesis and wound healing in db/db mice [ 131 ].…”
Section: Engineered Msc-evs In the Treatment Of Dm And Diabetic Compl...mentioning
confidence: 99%